Effect of Age on Attentional Control in Dual-Tasking. Issue 2 (15th March 2017) - Bier, Bianca; Lecavalier, Nick Corriveau; Malenfant, Dominique; Peretz, Isabelle; Belleville, Sylvie
Abstract : Background/Study Context: The age-related differences in divided attention and attentional control have been associated with several negative outcomes later in life. However, numerous questions remain unanswered regarding the nature of these age differences and the role of attentional control abilities in dual-tasking. The aim of this study was to evaluate the sources for age differences in dual-tasking and more specifically: (1) whether they occur because of differences in attentional control skills, or (2) whether the age-related decrement in dual-tasking is due to a general resource reduction that would affect the ability to complete any demanding task. Methods: In two experiments, young and older adults were required to combine an auditory digit span task and a visuospatial tracking task, for which performance was individually adjusted on each task. In Experiment 1, attentional control skills were measured by instructing participants to deliberately vary attentional priority between the two tasks. In Experiment 2, resource availability was measured by varying the level of difficulty of the visuospatial tracking task in a parametric manner by increasing the speed of the target to be tracked. Results: Both experiments confirmed the presence of a larger dual-task cost in older adults than in young adults. In Experiment 1, older participants were unable to vary their performance according to task instructions compared with younger adults. Experiment 2 showed that the age-related difference in dual-task cost was not amplified by a variation in difficulty. Conclusion: A marked age-related difference was found in the ability to control attentional focus in response to task instructions. However, increasing resource demand in a parametric manner does not increase the age-related differences in dual-tasking, suggesting that the difficulties experienced by older adults cannot be entirely accounted for by an increased competition for resources. A reduction in attentional control skills is proposed to account for the divided attention deficit reported in aging.